Here and now: perceptions of Indian Ocean islanders on the climate change and migration nexus. Issue 3 (3rd July 2017) - Kelman, Ilan; Upadhyay, Himani; Simonelli, Andrea C.; Arnall, Alex; Mohan, Divya; Lingaraj, G. J.; Nair, Shadananan; Webersik, Christian
ABSTRACT: Empirical studies exploring the links between climate change and migration are increasing. Often, perceptions are not fully explored from the people most affected by the climate change and migration nexus. This article contributes to filling this gap by eliciting and analysing perceptions regarding climate change and migration from an understudied population labelled as being amongst those most immediately and directly affected by climate change: Indian Ocean islanders. Open-ended, semi-structured interviews were conducted in two case-study communities in Maldives (Kaafu Guraidhoo with 17 interviews and Raa Dhuvafaaru with 18 interviews) and two case-study communities in Lakshadweep, India (Kavaratti with 35 interviews and Minicoy with 26 interviews). The results present the interviewees' perceptions of climatic variability and change that they experience; how they perceive the causes of these changes; and links to migration decisions. The interviews demonstrate that perceptions of climate change, of migration, and of the links or lack thereof between the two are centred on the interviewees' own experiences, their own locations, and the immediate timeframe. External information and direction have limited influence. Their perceptions are framed as being the 'here and now' through topophilia (here) and tempophilia (now). The islanders' views do not avoid, but rather encompass, long-term livelihoods and the future. Such a future might be in another location, but the anchor is expressing future hopes and aspirations through the here and now. It is not linked to the wide-scale, long-term issue of climate change.